ACCOUNTING FOR FUNCTIONAL DEPRECIATION. - Taggart, Herbert F. (The Accounting Review, 1940)
The article presents a comment on a previous article that appeared in the journal The Accounting Review. The presentation of an author's paper on obsolescence at Philadelphia, Pennsylvania last winter and its publication in the June issue of the journal The Accounting Review represent long overdue attention to this important subject by accountants. It is to be hoped that this paper is the beginning of really adequate attention to this subject, and that the author's other writings will shortly see the light of day in published form. At first glance the proposal that obsolescence should be accrued separately from the physical factors in what accountants commonly lump together under the head of "depreciation" is likely to arouse no great enthusiasm in the mind of the orthodox accountant. In spite of the rather gloomy picture of the present status of depreciation accounting presented in the article, or perhaps because of it, the impression should not be created that improvements cannot be expected. Quite the contrary is true. Further inquiries into the causes of depreciation in an attempt to measure their relative importance are fully justified. The result will be improved determination of depreciation rates and a sounder approach to the problems of managerial control.